2019
DOI: 10.1155/2019/7597382
|View full text |Cite
|
Sign up to set email alerts
|

Infiltration of Blood-Derived Macrophages Contributes to the Development of Diabetic Neuropathy

Abstract: Background and Objective. Diabetic neuropathic pain (DNP) is a common complication associated with diabetes. Currently, its underlying pathomechanism remains unknown. Studies have revealed that the recruitment of blood monocyte-derived macrophages (MDMs) to the spinal cord plays a pivotal role in different models of central nervous system injury. Therefore, the present study aimed at exploring the infiltration and function of MDMs in DNP using a mice model. Methods. Diabetes was induced using streptozotocin in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…CD45 expression analysis confirmed the infiltration of CD45 hi CD11b + macrophages at 12 wk in a murine neuropathy model induced by LP‐BM5 virus infection 23 . Flow cytometry also showed that the infiltration into the spinal cord began in 2 wk after streptozotocin injection in the murine diabetic neuropathic pain model 24 . Both activated microglia and macrophages in the spinal cord are involved in neuroplasticity by inducing and modulating cellular responses and contribute to neuroinflammation, 14 for the establishment or maintenance of pain.…”
Section: Spinal Microglia and Painmentioning
confidence: 76%
“…CD45 expression analysis confirmed the infiltration of CD45 hi CD11b + macrophages at 12 wk in a murine neuropathy model induced by LP‐BM5 virus infection 23 . Flow cytometry also showed that the infiltration into the spinal cord began in 2 wk after streptozotocin injection in the murine diabetic neuropathic pain model 24 . Both activated microglia and macrophages in the spinal cord are involved in neuroplasticity by inducing and modulating cellular responses and contribute to neuroinflammation, 14 for the establishment or maintenance of pain.…”
Section: Spinal Microglia and Painmentioning
confidence: 76%
“…Depletion of the two MΦ populations by the homodimerizer agent, AP20187, in MaFIA mice abolished the mechanical/cold hypersensitivity and spontaneous nociception. In neuropathic pain models, including partial nerve injury (6,35), constriction of the infraorbital nerve (5), and diabetic neuropathy (36) nor mechanical/cold hypersensitivity. Additional evidence that cancer-evoked mechanical/cold hypersensitivity and spontaneous nociception is dependent on rMΦs was obtained in MΦ-depleted MaFIA mice, whose tumor microenvironment, but not the nerve bundle, was replenished with peritoneal MΦs from donor mice.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this notion, clinical trials aimed at inhibiting IL-1β in T2DM patients showed improved β-cell function [ 247 ]. With regard to DPN, diabetes-induced neuropathy is associated with infiltration of blood-derived macrophages in the spinal cord [ 275 ], a proinflammatory phenotype of blood monocyte-derived macrophages [ 276 ] and activated spinal microglia [ 277 ].…”
Section: Mechanisms Linking Amyloid and Peripheral Neuropathymentioning
confidence: 99%